Systematic Review of University Research Hotbeds as a Training Intervention - Castro-Rodríguez, Yuri (2022)
This review compiles the information related to implementing research hotbeds as formative research strategies regarding higher university education. A systematic review-type study was designed. Methodologically, the databases Scopus, Web of Science, SciELO, Redalyc, MEDLINE (PubMed), ERIC and academic Google were investigated, using the terms: "Research hotbeds", "programs", "research skills" and "undergraduate student". Of the 235 sources initially searched, 22 references were analyzed (17 original articles and 5 theses). The information was analyzed according to the categories of place of publication, objectives, methods and results found. Studies were found with the qualitative approach (68.2%), others the quantitative approach (27.3%) and others a mixed approach (4.5%). Implementing a seedbed has a positive influence on the enhancement of research capabilities, achieving greater motivation among seedlings and better learning related to research methodology. Several studies found that the interrelation between teachers and students that is achieved in a nursery facilitates the learning of research and highlights the role of the student's protagonist, representing a leader in their pedagogical development. It is concluded that a university research seedbed is a learning community whose purpose is to encourage the research culture and the training of competencies in its members; The interventions carried out with the seedbeds have evidenced an improvement in research skills and an increase in student scientific production.